1996
DOI: 10.1002/j.2161-1920.1996.tb00434.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Career Maturity and Congruence, Consistency, and Differentiation Among Individuals With and Without Learning Disabilities

Abstract: This study investigated the relationship between career maturity and Holland's (1985a) constructs of congruence, consistency, and differentiation among individuals with and without learning disabilities. In addition, it examined whether a relationship exists between Holland's (1985a) Investigative personality type and career maturity in individuals with and without learning disabilities. Results yielded no statistically significant associations between career maturity and any of the 3 constructs for either gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
(22 reference statements)
1
11
1
1
Order By: Relevance
“…Adjudicated students with learning disabilities seem to be especially deficient at using problem-solving skills and making realistic decisions about vocational choices. These findings are consistent with the results of some previous investigations (Ohler & Levinson, 1996).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Adjudicated students with learning disabilities seem to be especially deficient at using problem-solving skills and making realistic decisions about vocational choices. These findings are consistent with the results of some previous investigations (Ohler & Levinson, 1996).…”
Section: Discussionsupporting
confidence: 94%
“…The eight subscales of the school form have adequate internal consistency (Cronbach's coefficient alpha), and coefficients range from 0.53 to 0.90 based on data for 668 high school students. In a previous study, Ohler and Levinson (1996) reported adequate reliability for the scales CP (.84), CE (.78), WW (.84), CDA (.84), CDK (.86), and COT ( 3 5 ) . Finally, the CDI has been shown to have adequate construct and concurrent validity, as determined by factor analysis and correlation with other measures of career maturity (Kapes, Mastie, & Whitfield, 1994;Savickas, 199% Thompson & Lindeman, 1981).…”
Section: Methodsmentioning
confidence: 87%
“…The match between career interests and employment opportunities has been described by many career theories as a significant factor in career planning stages (Holland, 1997;Super, 1994) . This interest-job match, or congruence, has been studied in relation to career maturity (Ohler & Levinson, 1996), aspects of wellbeing (Meir, Melamed, & Dinur, 1995), and person-environment match (Thompson, Flynn, & Griffith, 1994) and has been used to explore employee and job retention in community employment programs (Beale & Holinsworth, 2002) .…”
Section: Transition Outcomes and Interest-job Matchmentioning
confidence: 99%
“…C areer maturity has been defined as the individuals ability to make appropriate career choices, including awareness of what is required to make a career decision and the degree to which ones choices are both realistic and consistent over time (Crites, 1978b;King, 1989;Ohler, Levinson, & Hays, 1996). Career maturity can also be defined as the extent to which an individual has acquired the necessary knowledge and skills to make intelligent, realistic career choices.…”
mentioning
confidence: 99%